Wound Care Management with Primary Dressing on Diabetic Foot Ulcers Patients: A Case Study - Resty Enjelia ibrahim; Haeril Amir; Andi Mappanganro; David G Armstrong (PT.Mantaya Idea Batara, 2025)
Diabetic foot ulcers and diabetic ulcers are some of the consequences that diabetic patients often face. This study aimed to determine wound care using primary dressings on the feet of diabetic patients with tissue integrity problems. The method used in this study was a case study. This study utilized the intervention of treating diabetic foot ulcers of Mrs. J with primary dressings at the ETN Center Makassar Wound Care Home. This study was conducted with one respondent. After the diagnosis was established, the possible nursing intervention was to provide a primary dressing on the wound. After weekly patient wound care, I could see the changes. The visible changes were: The appearance of the scar will differ between the first and second visits. On the first visit, the wound looked like a thin serous exudate: 20%, epithelialized or pink: 70%. However, on the second visit, the wound looked like a thin serous exudate: 15%, epithelialized or pink: 85%. Based on the primary dressing wound care carried out, it can be concluded that primary epithelial cream wound care is effective in healing diabetic ulcers.